Adaptation of Medical College Students to the Learning Conditions with Different Educational Standards - Natalia I. Latyshevskaya; Galina A. Sevriukova; Natalia V. Levchenko; Elena N. Tikhonova (Журнал медико-биологических исследований)
A comparative analysis of heart rate variability (HRV) in medical college students following programmes according to the new educational standard (1 year and 10 months; n = 110) and those studying for 2 years and 10 months (n = 162) was conducted. HRV parameters were recorded using the VNS-Spectrum device (Neurosoft, Russia). We found that the intensification of the educational process overstrains the regulatory mechanisms of cardiac activity in students following programmes of 1 year and 10 months. This demonstrates the importance of using HRV as an indicator of students’ adaptation to the learning process, taking into account the educational standard, as well as the need to develop preventive measures.